Flow cytometry detection of planktonic cells with polycyclic aromatic hydrocarbons sorbed to cell surfaces. Issue 1 (15th May 2017) - Cerezo, Maria I.; Linden, Matthew; Agustí, Susana
Abstract: Polycyclic aromatic hydrocarbons are very important components of oil pollution. These pollutants tend to sorb to cell surfaces, exerting toxic effects on organisms. Our study developed a flow cytometric method for the detection of PAHs sorbed to phytoplankton by exploiting their spectral characteristics. We discriminated between cells with PAHs from cells free of PAHs. Clear discrimination was observed with flow cytometer provided with 375 or 405 nm lasers in addition to the standard 488 nm laser necessary to identify phytoplankton. Using this method, we measured the relationship between the percentages of phytoplankton organisms with PAHs, with the decrease in the growth rate. Moreover, the development of this method could be extended to facilitate the study of PAHs impact on cell cultures from a large variety of organisms. Graphical abstract: Highlights: New flow cytometric method for the detection of PAHs sorbed to cells. UV lasers allowed discriminate cells with PAHs sorbed from cells free of PAHs. Percentage of cells with sorbed PAHs increased with dosage and time. As the percentage of cells with PAHs increased, population growth rate decreased.